The Effect of Profitability, Liquidity and Leverage on Profit Growth with Firm Size as Intervening Variable in Healthcare Sector Companies on the Indonesia Stock Exchange - Agung, RZ. M. Febri; Fatimah, Fatimah; Choiriyah, Choiriyah (International Journal of Finance Research, 2025)
This study examines the effect of profitability, liquidity, and leverage on company size and profit growth in the healthcare sector listed on the Indonesia Stock Exchange (IDX). Employing a quantitative research approach, the study utilizes numerical data and statistical analysis through path analysis to evaluate the relationships among variables. The population comprises 30 companies in the pharmaceutical and healthcare subsectors, with 15 firms selected as samples using purposive sampling based on the completeness of financial data from 2019 to 2023. Secondary data were collected from published financial reports available on the IDX website (www.idx.co.id). The findings reveal that profitability has a significant effect on company size, while liquidity and leverage do not. Furthermore, profitability significantly influences profit growth, whereas leverage and company size show no significant effect on profit growth. The study suggests that healthcare sector companies should consider company size as a relevant factor for enhancing profit growth, as it demonstrates a positive relationship with profitability performance. These results contribute to understanding the financial dynamics influencing corporate growth within Indonesia’s healthcare industry.